MEDIA PEMBELAJARAN CANVA UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS VII SMP HKBP BELAWAN - Roulina Indri Yani Marpaung; Siregar, Elsa Siregar; Annisa; Ayu Indari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to explain the benefits of Canva media as a teaching medium in improving descriptive text writing skills. The study applies a classroom action research method accompanied by data collection techniques, namely observation, documentation, tests, and interviews. The subjects of the study included 24 students of class VII-2 SMP HKBP Belawan. The variables of this study are the learning process and the results of writing descriptive texts using Canva media. The results of this study in the pre-cycle showed that the minimum completeness standard that had been determined at 70 had not been met. The average pre-cycle score was 63.95, cycle I reached 68.25, with a success percentage of 62.5%, then an increase was seen in the second cycle with a score reaching 75.58, with a completion percentage that increased to 87.5%. Researchers can conclude that students of class VII-2 SMP HKBP Belawan have descriptive text writing skills that have improved after using Canva-based learning media.